West syndrome: long-term outcomes depending on etiology and treatment (literature review) - T. M. Prygunova (Русский журнал детской неврологии, 2019)
West syndrome is a severe form of childhood epilepsy associated with drug-resistant seizures and intellectual disability. The disease  is characterized by specific seizures called infantile spasms, hypsarrhythmia on the electroencephalogram, and delayed psychomotor development. The identification of the disease etiology may affect the prognosis and the choice of therapy. The following prognostic factors have been described so far: etiology, abnormal neurological signs, presence of other epileptic seizures before and after epileptic spasms, response to therapy regardless of the drug type. Difficulties associated with the diagnosis of West syndrome and long-term examination in outpatient settings lead to persistence of hypsarrhythmia and worsen the prognosis. Lack of universal standards for IS therapy results in significant diffe rences in treatment outcomes observed in different regions. Despite significant efforts made towards studying West syndrome, many aspects are still poorly understood. Further studies are needed to help physicians in choosing an optimal treatment strategy and appropriate duration  of follow-up as well as to improve the disease prognosis.